Genome and epigenome of a novel marine Thaumarchaeota strain suggest viral infection, phosphorothioation DNA modification and multiple restriction systems. (26th May 2017) - Ahlgren, Nathan A.; Chen, Yangyang; Needham, David M.; Parada, Alma E.; Sachdeva, Rohan; Trinh, Vickie; Chen, Ting; Fuhrman, Jed A.
Summary: Marine Thaumarchaeota are abundant ammonia‐oxidizers but have few representative laboratory‐cultured strains. We report the cultivation of Candidatus Nitrosomarinus catalina SPOT01, a novel strain that is less warm‐temperature tolerant than other cultivated Thaumarchaeota. Using metagenomic recruitment, strain SPOT01 comprises a major portion of Thaumarchaeota (4–54%) in temperate Pacific waters. Its complete 1.36 Mbp genome possesses several distinguishing features: putative phosphorothioation (PT) DNA modification genes; a region containing probable viral genes; and putative urea utilization genes. The PT modification genes and an adjacent putative restriction enzyme (RE) operon likely form a restriction modification (RM) system for defence from foreign DNA. PacBio sequencing showed >98% methylation at two motifs, and inferred PT guanine modification of 19% of possible TGCA sites. Metagenomic recruitment also reveals the putative virus region and PT modification and RE genes are present in 18–26%, 9–14% and <1.5% of natural populations at 150 m with ≥85% identity to strain SPOT01. The presence of multiple probable RM systems in a highly streamlined genome suggests a surprising importance for defence from foreign DNA for dilute populations that infrequently encounter viruses or other cells. This new strain provides new insights into the ecology, including viral interactions, of this important group of marine microbes.